(untitled) (African Journal of Biomedical Research, 2023)
Increased generation of reactive oxygen species has been reported during cyanide exposure, and quercetin, a flavonoid present in onions, has been proven to protect against it. Following sub-acute cyanide exposure, the protective effect of quercetin was investigated in the livers of rats in this study. Thirty male Wistar rats were grouped into 5 groups (n=6). Group 1 was administered conoil (control). Groups 2, 3, 4, and 5 were administered 7mgKCN/kgbwt/day, 60mg quercetin/kgbwt/day, 60mg Quercetin/kgbwt/day + 7mgKCN/kgbwt/day, and 600mg Na2S2O3/kgbwt/day+ 7mgKCN/kg bwt/day respectively for 2 weeks. Groups 4 and 5 were pre-administered with 600mg Na2S2O3/kg bwt/day and 60mgQuercetin/kgbwt/day respectively for 2 weeks. Activities of enzymes; Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), and Gamma-glutamyltransferase (GGT) in serum were measured as indicators of liver function. Liver malondialdehyde (MDA) and antioxidant parameters were assessed as indices of oxidative stress. When cyanide-treated rats were compared to control rats, serum ALT, AST, GGT, and liver MDA were considerably higher. Antioxidant parameters decreased significantly as a result of this. When quercetin and Na2S2O3 were given together, the liver function indices, liver MDA, and antioxidant markers all improved. Finally, the findings imply that quercetin protects the liver against cyanide-induced oxidative stress. These might be linked to an increase in the antioxidant state of the liver in cyanide-exposed rats